Treatment Pattern of Patients with Narcotics and Psychotropic Abuse (Case Study at the Bandung Rehabilitation Clinic) - Sergeonery, Lively (Indonesian Journal of Pharmaceutical Research, 2021)
Narcotics, psychotropics, and addictive substances abuse can cause addiction, which is a chronic disorder characterized by compulsive drug seeking and use despite adverse consequences. This is a concurrent descriptive study carried out by evaluating medical records and MMAS-8 questionnaire for assessing patients’ adherence. In addition, therapeutic success and quality of life were also evaluated using WHOQOL-BREF questionnaire. The study took place in the period of September-November 2018 at Medika Antapani Clinic. Data collected from patients under drug maintenance was used to identify the types of drug mostly used by the patients and their treatment, assess the impact of the management, and identify factor influencing therapeutic success. The results showed that there were 40 drug abusers at Medika Antapani Clinic. The abused drugs were amphetamine (80%), cannabis (72%), heroin (35%), benzodiazepine (25%), and nitrazepam (20%). Therapeutic measures used to treat drug abuse were alprazolam in 38 patients (95%), clonazepam in 33 patients (82.5%), nitrazepam in 29 patients (72.5%), lorazepam in 22 patients (55%), and diazepam in 14 patients (35%). Drug rehabilitation patients had low adherence of only 50%. Measurement of quality of life revealed social relation as the dimension with the highest score of 69 + 20.44, with most patients categorized as having moderate quality of life. Therapy with benzodiazepine has potential to cause dependence so it must be practiced with caution.